Language and culture in health communication in an emergency context: do health practitioners and patients talk differently about uncertainty and risk? - Nissen, Vanda; Meuter, Renata F. I. (Frontiers in Communication, 2023)
Abstract Objective: To explore how expressions of uncertainty are used and understood by patients and their health practitioners (HPs) in language concordant vs language discordant consultations, and to invoke CAT to identify the use of communication strategies, with a focus on HPs. Methods: This qualitative study encompassed 15 transcribed video and audio recordings of medical consultations between monolingual and bilingual patients and HPs captured in an Australian Emergency Department (ED). HPs and patients also completed a Language Background Questionnaire (LBQ).The main outcome measures included the number and type of expressions of risk and uncertainty used by patients and HPs, and strategies used by HPs to accommodate to their patients’ conversational needs. Results: Fifteen representative conversations were analyzed, involving two bilingual and two monolingual HPs and 14 patients (of whom 5 were bilingual). All conversations contained epistemic expressions (e.g., probably), which were used more frequently by patients and more often by bilingual patients. HPs accommodated effectively overall, but some bilingual patients showed difficulties in their understanding. Conclusions: All interlocutors expressed uncertainty to varying degrees. The greater use of uncertainty expressions by (bilingual) patients suggests that HPs could increase their communicative effectiveness by attending specifically to their patients’ uncertainty talk. Such talk may reflect a need for reassurance. For culturally and linguistically diverse patients it may reflect issues with comprehension.